2017
DOI: 10.1038/s41598-017-05875-z
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 localizes at the centrosome and midbody and is required for faithful cell division

Abstract: The cyclin-dependent kinase-like 5 (CDKL5) gene has been associated with rare neurodevelopmental disorders characterized by the early onset of seizures and intellectual disability. The CDKL5 protein is widely expressed in most tissues and cells with both nuclear and cytoplasmic localization. In post-mitotic neurons CDKL5 is mainly involved in dendritic arborization, axon outgrowth, and spine formation while in proliferating cells its function is still largely unknown. Here, we report that CDKL5 localizes at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Each compound and its target are labeled and closely clustered compounds with labeled common mechanisms are grouped by colors. b Compounds in cluster IV arranged based on the functions of their targets during cell cycle 21 33 . CDK7 and ERCC3, being part of TFIIH complex, are involved in DNA repair 34 .…”
Section: Resultsmentioning
confidence: 99%
“…Each compound and its target are labeled and closely clustered compounds with labeled common mechanisms are grouped by colors. b Compounds in cluster IV arranged based on the functions of their targets during cell cycle 21 33 . CDK7 and ERCC3, being part of TFIIH complex, are involved in DNA repair 34 .…”
Section: Resultsmentioning
confidence: 99%
“…The other three variants p.Arg326Gln, p.Glu660Gly and p.Arg1862* caused a two-fold increase in such defects. It is of interest to note that centrosomal and cell cycle proteins like CDKL5 (Barbiero et al, 2017) and EFHC1 (de Nijs et al, 2012) have been previously reported for human epilepsy syndromes. ZGRF1 variants identified in this study provide genetic evidence and preliminary insights into hitherto unanticipated roles of this protein associated with HWE.…”
Section: Discussionmentioning
confidence: 99%
“…A case‐in‐point are the cyclin‐dependent kinase‐like (CDKL) kinases, a small family of five poorly characterised and structurally distinct Ser/Thr protein kinases from the CGMC evolutionary branch of the kinome, which contains GSK3α, MAPK and CDK families (Canning et al , ). Mammalian CDKL5 (also known as STK9) is widely expressed in cells, where it is targeted to a variety of subcellular structures (Barbiero et al , ; Oi et al , ). Of particular interest, inactivation of the X‐linked CDKL5 gene, or disease‐associated mutations commonly found in the N‐terminal CDKL5 catalytic domain, causes a neurodevelopmental disorder termed CDKL5 deficiency disorder (CDD; Tao et al , 2004; Weaving et al , 2004), which has some overlapping features with Rett syndrome (Scala et al , ) and West syndrome (Kalscheuer et al , ).…”
Section: Physiological Cdkl5 Substrates Control Cytoskeletal Functionmentioning
confidence: 99%